Green Meaning, Grey Mind: Lost Between Green and Good - Windy Eka Saputri (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This research focuses on exploring the extent to which ignorance, indifference, and responsible avoidance are associated with maladaptive coping mechanisms in green marketing and how these mechanisms affect consumer purchasing behavior towards green products. Considering the fact that consumers are becoming overwhelmed with sustainability messages and information to the point of actually undermining their intention to purchase green products, the relevance of this research becomes more apparent. Methodology: This study employed a theory synthesis to propose a research framework. The sustainability message led to avoidance behaviors; thus, the proposed framework provides an understanding of how mental and emotional strains affect the marketing of green products. Results: The study also highlights the fact that an overload of information, particularly in the context of green and sustainable marketing, serves as a boundary condition that results in the reverse of the desired outcomes. Findings: The research also provides a research model that demonstrates how the three types of avoidance-related behavior disengage consumers, representing an integrated framework. Novelty & Originality: The novelty of this study lies in its integrated examination of three distinct avoidance-related behaviors within a single framework in the context of green marketing, an approach rarely undertaken in prior research. Its originality emerges from the application of theory synthesis to connect maladaptive coping mechanisms with consumer disengagement. Conclusions: Finally, the research reaffirms that to avoid the aforementioned maladaptive behaviors, the target audience of green products should be provided with simplified, relevant, and clear messages. Type of Paper: This paper is an empirical research paper.